PENEGAKAN HUKUM TERHADAP PENJUAL LIQUEFIED PETROLEUM GAS 3 KILOGRAM YANG MENJUAL DIATAS HARGA ECERAN TERTIGGI OLEH KEPOLISIAN RESOR TOBA SAMOSIR - Septamor Simanjuntak; Dessy Artina; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The sale of Liquefied Petroleum Gas 3 kilograms above retail price the highest was a serious disservice to consumer communities. It was necessary to establish a rule on the highest retail price imposed by governments to prevent the sale of Liquefied Petroleum Gas 3 Kilogrmas over the highest retail price. In article 10 points a law No. 8 of 1999 on protection the Consumer claims that the perpetrators in the attempt to promote, advertise or make incorrect or misleading statements about the price or price of an item or a service. Ut in fact there are still lots of bases that sell LPG 3 Kilograms race above the highest retail price. This type of study would be considered a sociological law study in order to see the effect a positive legal product may have on people’s lives. The study is also a graphic characterization of the law as a social control with regard to the creation and maintenance of the referrals with a foothold of the legal ability to control human behavior and create an agreement in the behavior of the Toba Samosir Resort Police Station and several bases LPG 3 Kilograms. From what this study has shown is that law enforcement is against seller of Liquefied Petroleum Gas 3 kilograms in Toba Samosir region by the Toba Samosir police hasn’t been very good. It is because the Toba Samosir police resort don’t take too much of a hit surveilance, so there are still a lot of vendors that sell higher of the highest retail price. As for the constraints that investigators face the police force is both internal and external factors. Efforts made to overcome these obstacles by establishing cooperation with the Agency Industrialization and Commerce Toba Samosir, sicialization of owners, Resort police investigators training. Keywords: Law enforcement-The Highest Retail Price-LPG 3 Kilograms